ROLE OF THE INDEPENDENT COMMISSIONER IN RELATIONSHIP FAMILY OWNERSHIP AND COMPANY SIZE ON COMPANY VALUE - Paulus Tangke (Institut Transparansi dan Akuntabilitas Publik (INSPIRING), 2022)
Purpose – This study aims to examine the moderating role of the Independent Commissioner in the relationship between Family Ownership and Firm Size on Firm Value. Design/methodology/approach – The method used in this study is the Moderation Regression Analysis method. Findings – The results of this study indicate that family ownership has a negative and insignificant effect on firm value. Firm size has a positive and significant effect on firm value. Independent Commissioners can moderate the relationship between Family Ownership and Firm Value. Likewise, the Independent Commissioner able to moderate the relationship between Firm Size and Firm Value. Originality – The data source in this study is the annual report of manufacturing companies listed on the Indonesia Stock Exchange for the period 2017 to 2019.